Personal Hygiene Genetalia Relationship With Leucorrhoea Event On Aliyah Student of Ulul Albab Islamic Boarding School - Husna (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2021)
Vaginal discharge often occurs in women, including teenagers. Teenagers who do not maintain the cleanliness of the genital area are at risk of experiencing genital problems such as vaginal discharge. The purpose of this study was to determine the relationship of personal genital hygiene with the incidence of vaginal discharge in female students of Aliyah Pondok Pesantren Ulul Albab Koto Baru, Dharmasraya Regency. While the method used in this research is using the analytical survey method and using cross-sectional. The sampling method is using a total sampling of 44 respondents. The results obtained using the chi-square test obtained p-value = 0.034 <0.05. There is a significant relationship between genital personal hygiene and the incidence of vaginal discharge.